Application of network pharmacology in traditional Chinese medicine for the treatment of digestive system diseases - Zheng, Shihao; Liang, Yijun; Xue, Tianyu; Wang, Wei; Li, Size; Zhang, Peng; Li, Xiaoke; Cao, Xu; Liu, Qiyao; Qi, Wenying; Ye, Yongan; Zao, Xiaobin (Frontiers in Pharmacology, 2024)
With the general improvement of living standards in recent years, people's living habits, including their diet habits, have changed. More people around the world have not followed a healthy diet, leading to an increase in the morbidity and even mortality of digestive system diseases, which showed a rising trend year by year. The advantage of traditional Chinese medicine (TCM) in treating digestive system diseases is evident. Consequently, the mechanisms of action of single Chinese herbs and compound Chinese medicines became research hotspots. The research method of the network pharmacology system was highly consistent with the holistic concept of TCM, providing a new perspective and theoretical basis for the basic research of digestive system diseases. This article summarized the common databases currently used in research on TCM. It also briefly introduced the basic methods and technologies of network pharmacology studies. The article summarized the advancements in network pharmacology technology through a comprehensive literature search on PubMed. Based on this analysis, we further explored the role of TCM in treating digestive system diseases, including chronic gastritis, gastric cancer, ulcerative colitis, and liver cirrhosis. It provides new ideas and references for treating digestive system diseases with TCM in the future and serves as a reference for relevant researchers.